Full Valley and Spin Polarizations in Strained Graphene with Rashba Spin Orbit Coupling and Magnetic Barrier - Wu, Qing-Ping (Sci Rep, 2016)
We propose a graphene-based full valley- and spin-polarization device based on strained graphene with Rashba spin orbit coupling and magnetic barrier. The underlying mechanism is the coexistence of the valley and single spin band gaps in a certain Fermi energy. By aligning the Fermi energy in the valley and single spin band gaps, remarkable valley- and spin-polarization currents can be accessed.